Dietary and non-dietary risk factors associated with excess body mass and abdominal obesity in adolescents from rural regions of southern Poland: a cross-sectional study - Błaszczyk-Bębenek, Ewa; Holko, Przemysław; Kawalec, Paweł; Piórecka, Beata (Frontiers in Public Health, 2025)
Excess body mass, including abdominal obesity, has multifactorial causes that are closely linked to various aspects of child development. The prevalence of excess body mass in the pediatric population in Poland is increasing. This study aimed to assess risk factors for excess body mass, including abdominal obesity, among adolescents from southern Poland. A total of 381 adolescents were included to determine the prevalence of overweight and obesity based on body mass index (BMI ≥ 85th percentile) and of abdominal obesity based on waist-to-height ratio (WHtR ≥0.5). Lifestyle habits, along with dietary and sociodemographic data, were assessed as independent risk factors for excess body mass and abdominal obesity using regression analysis. Excess body mass and abdominal obesity were reported in 17 and 8.1% of participants and were positively correlated with body dissatisfaction, fear of becoming obese, physical exercise after eating to prevent weight gain, following a weight-loss diet, receiving comments about one’s appearance, accepting one’s figure but starting a diet due to environmental or media pressure, and more frequent snacking. Excess body mass was positively correlated with low physical activity at school, while abdominal obesity was linked to a less health-promoting diet. Our study indicates the presence of several modifiable risk factors associated with excess body mass and abdominal obesity. These findings may help guide future multifactorial prevention strategies aimed at reducing obesity and its long-term consequences in adulthood.